An Example in Remote Computing Over the Internet applied to Geometry - Ferreira, M.; Casquilho, M. (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2020)
Scientific computing over the Internet can suit many activities that have not, in the authors’ opinion, been explored enough in general. Resources such as executables, languages, packages, can be used from a remote computing system. In this study, largely based on academic practice, a simple illustrative example in Geometry is implemented on a distributed system that outsources the computing-intensive tasks to remote servers that may be located in other universities or companies, linked to grids and clusters and so on. The software stack and software developed to support the communication is explained in detail. The architecture developed stresses the interoperability of the software, and a suitable high degree of decoupling between components hosted in various locations. The results of this study motivate further work and serve a practical purpose that may be useful to everyone doing scientific computing.
Keywords: internet; remote executables; scientific computing; university-industry links; IJIMAI